Method for removal of tooth decay preferred by dentist and children patients - Zaida Moya de Calderón (2019)
We performed a comparative analytical study in order to determine the preference it dentists and patients on the clinical use gel with the enzyme papain obtained from Carica pubescens versus conventional rotary method for the removal of tooth decay in children. The research began with pilot-scale production of enzyme gel remover Carica pubescens.To determine the preference of the removal of caries validated questionnaires were applied pretest and posttest to 308 dentists and 308 patients randomly selected children who participated voluntarily, from cities in southern Peru. The dentists were trained in patient selection, the diagnosis of tooth decay, the inclusion and exclusion criteria and clinical application technique of gel. At random was used gel or conventional rotary method at the mouth of a patient with similar clinical features of two oclusal carious lesions and at successive times. Also applied a scale for clinical assessment in determining the effectiveness of the gel by dentists. The results show that dentists and patients prefer the enzyme gel Carica pubescens for the removal of caries, compared to conventional rotary method (p<O.OO1) and rating scale perceived by the dentist is also satisfactory for use clinician. We conclude that Carica pubescens gel can be used in enzymatic removal of tooth decay, with minimal clinical intervation and patient comfort, making a positive psychological impact for the acceptance of dental treatment in children.